Trap tales: The influence of red alder stand conditions and forest fragmentation on family-level beetle bycatch diversity - Ting Ting Michelle Yim; Sichen Zhou; Debra L. Wertman; Allan L. Carroll (PLoS ONE, 2026)
Beetle (Coleoptera) bycatch from insect traps can provide insights into forest health and biodiversity trends. Red alder, Alnus rubra , a nitrogen-fixing tree that supports high invertebrate diversity, is facing alder bark beetle-associated declines and increasing fragmentation in coastal British Columbia (BC), Canada. Despite these threats, no research has investigated beetle diversity or its responses to stand conditions and fragmentation in red alder ecosystems. We hypothesized that in red alder ecosystems, (1) stand conditions influence beetle family bycatch diversity through habitat and food availability, and (2) forest fragmentation influences beetle family diversity by altering habitat connectivity and patch size. We also evaluated how these factors affect abundances of select scolytine predatory families (Salpingidae, Monotomidae, Nitidulidae, Staphylinidae, and Histeridae). Ethanol-baited multiple-funnel traps ( N = 25) targeting ambrosia beetles were deployed in five red alder-dominated forests in southwestern BC in 2024. Beetle bycatch ( N = 8226 individuals) was identified to family and determined to be predominantly saproxylic. Family-level Shannon Diversity Index ( H’ ), richness, and select abundances were compared between sites, and their relationships with stand conditions and fragmentation analyzed using bivariate models. Site-level differences were observed for H’ , richness, and abundances, all of which were associated with stand conditions and fragmentation to varying extents. Notably, higher tree density and abundance of dead red alders and lower fragmentation were associated with higher beetle bycatch diversity. Structural heterogeneity, including deadwood availability, and forest continuity likely provided microhabitats supporting saproxylic beetle families in these forests. Examining beetle diversity at the family level allowed us to explore functional associations of saproxylic beetles to environmental conditions across landscapes, although these associations should be interpreted judiciously due to coarse taxonomic resolution and sampling and analytical limitations. Beetle bycatch resolved to family level represents a valuable resource for biodiversity monitoring and conservation management in red alder forests.